1996
DOI: 10.1097/00003246-199607000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Plasma antioxidant potential in severe sepsis

Abstract: Plasma antioxidant potential is initially decreased in patients with sepsis who develop organ dysfunction, and it increases over time. While we have no clear evidence to prove that this reduction has a causal relationship, failure to achieve a normal plasma antioxidant potential is strongly associated with an unfavorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(40 citation statements)
references
References 26 publications
1
38
1
Order By: Relevance
“…The present study contrasts with the findings of Cowley et al [34] who found antioxidant levels to be higher in survivors than non-survivors of severe sepsis at 5–7 days following ICU admission. This may reflect differences in the patient cohort as none of the patients in the study by Cowley et al had surgical intervention for sepsis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present study contrasts with the findings of Cowley et al [34] who found antioxidant levels to be higher in survivors than non-survivors of severe sepsis at 5–7 days following ICU admission. This may reflect differences in the patient cohort as none of the patients in the study by Cowley et al had surgical intervention for sepsis.…”
Section: Discussioncontrasting
confidence: 99%
“…Levels of the antioxidants SOD and catalase were found to be significantly reduced in patients with peritonitis in keeping with previous reports [34]. However, GSH-Px levels did not differ from healthy controls in the present study but were reduced in previous studies on septic patients [18, 35, 36].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, studies in adult population have shown contradictory results. Both lower [11] and higher [12][13][14] plasmatic antioxidant capacity have been reported in adult patients with SIRS and sepsis. These contradictory results can be explained by differences in the studied sample (total plasma, deproteinized plasma, or serum) and by the particular laboratory technique, which determines the relative contribution of each plasmatic antioxidant to the total antioxidant capacity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Despite endogenous anti-oxidant systems, this state feeds-forward in a self-sustaining fashion, amplifying individual organ failure and immune dysregulation. Of note, the degree of ‘oxidative stress’ (as measured in the plasma compartment) has been reported to influence outcome in critical illness(186, 187). As noted above, attempts to treat oxidative stress (quenchers: Vitamins A, C and E, melatonin, N-acetyl cysteine, glutamine; enzyme inhibitors: allopurinol, various NOS inhibitors; chelators: defuroxamine) have largely failed translation from model systems and case series to clinical trials.…”
Section: Anti-oxidant Therapiesmentioning
confidence: 99%